Association between short-term exposure to ambient air pollution and heart failure: An updated systematic review and meta-analysis of more than 7 million participants - Yang, Yu-shan; Pei, Ying-hao; Gu, Yuan-yuan; Zhu, Jun-feng; Yu, Peng; Chen, Xiao-hu (Frontiers in Public Health, 2023)
Exposure to air pollution has been linked to the mortality of heart failure. Here, we sought to update the existing systematic review and meta-analysis, published in 2013, to further assess the association between air pollution and acute decompensated heart failure including hospitalisation and heart failure mortality. Methods: PubMed, Web of Science, EMBASE and OVID databases were systematically searched till April 2022. The studies regarding air pollution exposure and heart failure were enrolled and extracted the original data to combine and obtain an overall risk estimate for each pollutant. Results: We analyzed 51 studies and 7,555,442 patients. Our results indicated that heart failure hospitalization or death was associated with increases in carbon monoxide (3.46% per 1 part per million; 95%CI 1.0233-1.046, P<0.001), sulfur dioxide (2.20% per 10 parts per billion; 95% CI 1.0106-1.0335, P<0.001), nitrogen dioxide (2.07% per 10 parts per billion; 95% CI 1.0106-1.0335, P<0.001), ozone (0.95% per 10 parts per billion; 95% CI 1.0024-1.0166 <0.001) concentrations. Increases in particulate matter concentration wer4e related to heart failure hospitalization or death (PM2.5 1.29% per 10μg/m³, 95% CI 1.0093-1.0165, P<0.001; PM10 1.30% per 10μg/m³, 95% CI 1.0102-1.0157, P<0.001). Conclusion: The increase of all pollutants including gases (carbon monoxide, sulfur dioxide, nitrogen dioxide, ozone) and particulate matter ([PM2.5], [PM₁₀]) are positively correlated with heart failure hospitalization rates and mortality.